2008
DOI: 10.1002/lt.21350
|View full text |Cite
|
Sign up to set email alerts
|

The effect of liver transplantation on autonomic dysfunction in patients with end-stage liver disease

Abstract: Autonomic dysfunction is a recognized complication of end-stage liver disease (ESLD), but there is little information on how liver transplantation (LT) affects this problem. We sought to prospectively evaluate autonomic function in patients with ESLD before and after LT. Autonomic reflex screen (ARS) was performed on 30 patients with ESLD prior to transplantation. A 10-point composite autonomic score (CAS) was calculated from these data. ARS was repeated after LT, and these scores were compared with the pre-LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 19 publications
(27 reference statements)
1
27
0
1
Order By: Relevance
“…44,45 About two-thirds of the patients with cirrhosis have an autonomic dysfunction before liver transplantation. 41,44,46 The prolonged QT interval reverses in about half of the patients after liver transplantation, probably as a result of diminished portosystemic shunting. 43,47,48 But in a minority of the patients, the QT interval may worsen after liver transplantation.…”
Section: Cardiac Function and Liver Transplantationmentioning
confidence: 98%
See 1 more Smart Citation
“…44,45 About two-thirds of the patients with cirrhosis have an autonomic dysfunction before liver transplantation. 41,44,46 The prolonged QT interval reverses in about half of the patients after liver transplantation, probably as a result of diminished portosystemic shunting. 43,47,48 But in a minority of the patients, the QT interval may worsen after liver transplantation.…”
Section: Cardiac Function and Liver Transplantationmentioning
confidence: 98%
“…43,47,48 But in a minority of the patients, the QT interval may worsen after liver transplantation. 46 In conclusion, liver transplantation is the ultimate treatment for patients with end-stage liver disease, but perioperatively it exerts a considerable stress on the cirrhotic heart. However, proper identification of patient at risk of developing cardiac failure is difficult.…”
Section: Cardiac Function and Liver Transplantationmentioning
confidence: 99%
“…was assigned to them [10]. The remaining two patients chose not to perform the 6mwt, and they were excluded from the gait speed analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have already indicated that the six minutes walking test (6mwt) is an adequate predictor of mortality in liver transplantation candidates [10,11] and hospital readmission in chronic heart failure [12]. Therefore, the possibility for using this approach to predict cardiac events in advanced liver disease should be considered as it is not neither expensive nor complicated to be carried out.…”
Section: Introductionmentioning
confidence: 99%
“…39 The degree of dysautonomia improves after liver transplantation in 63% of patients at 6-7 months; however in a very small number it gets worse despite successful grafting, 39 and in patients whose allograft function is impaired, dysautonomia persists. 40 Although the aforementioned studies had relatively short follow-up studies of spontaneous baroreflex sensitivity have shown improvements which remain at 18 months.…”
Section: Liver Transplantation (Lt) and Autonomic Functionmentioning
confidence: 99%